MEMBANGUN KEMANDIRIAN EKONOMI HIJAU MELALUI PEMBERDAYAAN USAHA KERIPIK PISANG DI DESA SIDOWUNGU KECAMATAN MENGANTI KABUPATEN GRESIK - Aristyanto, Erwan; Hariyanto, Krisnadhi; Anggraini, Desy Ismah (Universitas Mataram, 2025)
This community service activity supports one of the main focus areas of Community Service 2025, which is National Independence Based on Green Economy through the processing of banana peel and stem waste into organic fertilizer and providing partners with banana chip technology. The partner in this community service is Mr. Budi Sutiawan, the owner of Al-Maulana banana chip business, located in Sidowungu Village, Menganti, Gresik, which is 11 KM away from the UWP Campus. The urgency of this activity is the low production capacity and the poor quality of the products produced, thus requiring the touch of science and technology. The goal of this activity is to improve the production capacity and quality of the partner and increase the partner's turnover. Priority issues are as follows: in the Production sector; production equipment is still traditional and not ergonomic, wasteful of fuel, unhealthy, and not hygienic, storage areas are dirty and have many pests, workers do not wear personal protective equipment (PPE); in the Marketing sector; sales are unstable, packaging still uses thin plastic, labels and branding are less attractive, in the Business Management sector; there is no financial record and a lack of understanding of food safety. Proposed solutions include; improving capacity and product quality through the development of banana chip processing technology, enhancing business capabilities, expanding marketing reach, improving packaging, labels, and branding, and establishing financial records. The implementation method involves the development of a Banana Chip Machine Technology, training, mentoring, and partnerships. The results of the activities in this program include coordination of program implementation with partners, dissemination of Banana Chip Machine Technology, procurement of equipment and training for healthy production, dissemination of Compost Tube Technology for waste processing, training and mentoring for online and offline sales, training and mentoring for label and logo creation, and training and mentoring for recording business financial transactions. The impact of this activity includes a 30% increase in the capacity and quality of partner products, a 30% increase in partner revenue, and a 50% increase in partner knowledge and skills.